Genomic and phenotypic stability of fusion-driven pediatric sarcoma cell lines - Kasan, Merve; Geyer, Florian H.; Siebenlist, Jana; Sill, Martin; Öllinger, Rupert; Faehling, Tobias; de Álava, Enrique; Surdez, Didier; Dirksen, Uta; Oehme, Ina; Scotlandi, Katia; Delattre, Olivier; et al. (Nature Communications, 2025)
Human cancer cell lines are the mainstay of cancer research. Recent reports showed that highly mutated adult carcinoma cell lines (mainly HeLa and MCF-7) present striking diversity across laboratories and that long-term continuous culturing results in genomic/transcriptomic heterogeneity with strong phenotypical implications. Here, we hypothesize that oligomutated pediatric sarcoma cell lines mainly driven by a fusion transcription factor, such as Ewing sarcoma (EwS), are genetically and phenotypically more stable than the previously investigated adult carcinoma cell lines. A comprehensive molecular and phenotypic characterization of multiple EwS cell line strains, together with a simultaneous analysis during 12 months of continuous cell culture show that fusion-driven pediatric sarcoma cell line strains are genomically more stable than adult carcinoma strains, display remarkably stable and homogenous transcriptomes, and exhibit uniform and stable drug response. Additionally, the analysis of multiple EwS cell lines subjected to long-term continuous culture reveals that variable degrees of genomic/transcriptomic/phenotypic changes among fusion-driven cell lines, further exemplifying that the potential for reproducibility of in vitro scientific results may be rather understood as a spectrum, even within the same tumor entity.
Gesehen am 25.07.2025